Uncertainty Management for Robust Industrial Design in Aeronautics : Findings and Best Practice Collected During UMRIDA, a Collaborative Research Project (2013–2016) Funded by the European Union /: Findings and Best Practice Collected During UMRIDA, a Collaborative Research Project (2013–2016) Funded by the European Union. ([2019]) - Unknown
No abstract available